(untitled) (World Economics and Finance Bulletin, 2022)
The study aimed to demonstrate the effectiveness of the research organization in adopting the entrepreneurial marketing strategy as an independent variable that included three sub-dimensions (After focusing on the customer, managing risk, seizing opportunities), and the extent of its impact on achieving sustainable performance as a dependent variable that includes three dimensions (the social dimension, the economic dimension, the environmental dimension) and revealing the relationship and impact of pioneering marketing in achieving sustainable performance in a sample of telecommunications companies in Baghdad governorate, represented by Zain Iraq Telecom, which is considered one of the largest telecommunications companies with a clear majority in the number of users,As one of the pioneering and innovative companies in providing their services to customers and for collecting the necessary data, the questionnaire was adopted in addition to the adoption of the personal interviews method. A random sample of (80) employees of the company was selected. This study reached a set of conclusions, including the company’s ability to adapt to the changing and complex environment, seizing opportunities and working to achieve sustainable performance to enable it to survive in light of continuous changes, meet the needs of its customers, provide innovative services and offers, achieve customer satisfaction, and achieve superiority over competitors.